Keanekaragaman Jamur Makroskopis sebagai Bahan Ajar Pengayaan Biologi - Munarti Munarti; Rita Retnowati; Sri Ainiyyah Putri (Universitas Sebelas Maret, 2023)
Teaching materials are learning resources to help teachers and students achieve learning goals. Learning resources including enrichment teaching materials play an important role in supporting successful learning. The aim of this study was to produce valid biology enrichment teaching materials based on research on macroscopic fungal diversity at the Nature Conservation Education Center in Bodogol, West Java. This research is a qualitative descriptive study by describing based on the morphological characteristics of the types of macroscopic fungi that have been found at the research site, then arranged in the form of biological enrichment materials in the form of Student Worksheets (LKPD) on Mushrooms for class X SMA. The LKPD that has been prepared is tested for suitability by three validators which include aspects of content suitability, language suitability aspects, and appearance suitability aspects. The results showed that there were 79 species of macroscopic fungi found at the study site, some of the species found were used as enrichment material for LKPD for their morphological characteristics, classification and method of reproduction. The LKPD validation results obtained a score of 89% and were in the very valid category so they were suitable for use by students. The contribution of the results of this research to education can be an additional source of learning to enrich and improve students' understanding, especially on fungi.